Linear and Nonlinear Photon-Induced Cross Bridge/Space Charge Transfer in STC Molecular Crystals - Chen Lu; Jing Yu; Hao Sheng; Yongjian Jiang; Fengyang Zhao; Jingang Wang (Nanomaterials, 2022)
In this work, we theoretically studied the optical absorption properties of a layer-stacked cocrystal heterogeneous material Spe-TCNB cocrystal (STC) which is produced by supramolecular self-assembly of organic conjugated monomers SPE and TCNB. The highly ordered aggregate structure in the cocrystal STC will lead to intermolecular interactions such as π∼π, hydrogen bonds and van der Waals forces, resulting in significant charge transfer characteristics and large cross-sectional two-photon absorption characteristics. The physical mechanism of one-photon and two-photon charge transfer of cocrystal molecules is specifically discussed and the interaction between molecules and their role in charge transfer are quantitatively analyzed. We found that the charge transfer between molecular junctions composed of hydrogen bonds is mainly cross-bridge charge transfer, while the charge transfer between molecular junctions caused by accumulation is mainly cross-space charge transfer. This discovery is of great significance to the design of organic photoelectric functional materials.